Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.procs.2015.02.161
|View full text |Cite
|
Sign up to set email alerts
|

Open Issues in Software Defect Prediction

Abstract: Software Defect Prediction (SDP) is one of the most assisting activities of the Testing Phase of SDLC. It identifies the modules that are defect prone and require extensive testing. This way, the testing resources can be used efficiently without violating the constraints. Though SDP is very helpful in testing, it's not always easy to predict the defective modules. There are various issues that hinder the smooth performance as well as use of the Defect Prediction models. In this report, we have distinguished so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…Nevertheless, the challenge of unavailability of the local data faces the organization's team. The reasons for unavailability may be due to the changing of technology or no similar features of projects previously developed [1]. To overcome this problem, the cross-project software defect prediction is used.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the challenge of unavailability of the local data faces the organization's team. The reasons for unavailability may be due to the changing of technology or no similar features of projects previously developed [1]. To overcome this problem, the cross-project software defect prediction is used.…”
Section: Literature Surveymentioning
confidence: 99%
“…Nowadays, Software Defect Prediction (SDP) is very critical in software engineering and one of the most helping activities during the testing phase of the System Development Life Cycle (SDLC). However, predicting the defective modules isn't a straight forward job [1].…”
Section: Introductionmentioning
confidence: 99%
“…For predicting software defects the authors used multivariate analysis [16], [17] and showed that the accuracy of software quality prediction was not affected by decreasing independent factors. The authors also used zero-inflated Poisson Regression In paper [14], an aggregate of problems was discussed with existing state-of-the-art defect prediction approaches. The authors identified the problems as follows: i) they found the set of attributes to be correlated with fault, ii) there is an absence of standard measures for performance assessment, iii) there are problems with cross project defect prediction, iv) there are inconsistencies with the economics of software defect prediction, v) the class imbalance problem and vi) the absence of any general framework for the software defect prediction.…”
Section: Related Workmentioning
confidence: 99%
“…This allowed a direct comparison of the different approaches proposed in literature [12], [13]. Six issues with existing state-of-the-art techniques were discussed in [14] and while there have been a few papers that try to address the issues raised in the paper, some of the core problems still remain. However, these approaches did not address imbalanced data, thus being less effective for real world problems.…”
Section: Introductionmentioning
confidence: 99%
“…Complexity metric selection as attributes or features in software defect detection still be an issue today. Not all of complexity metric influent the occurrence of software defect [3]. It needs a method to select the most influential complexity metrics.…”
Section: Introductionmentioning
confidence: 99%